High efficiency light enhancement film modified with antireflection coating and method of making same

CN122898012APending Publication Date: 2026-10-13深圳市诺保科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611000591.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了抗反射涂层修饰的高效增光膜及其制造方法,解决了现有增光膜抗反射层因固化收缩与组分相分离导致附着力差、雾度高,以及在卷对卷连续制造中因内应力积聚引起薄膜收卷翘曲开裂的问题

Benefits of technology

1、本发明通过全氟聚醚聚氨酯丙烯酸酯与时序固化工艺中前序烘箱正压环境的配合,在交联网络大规模构建前利用动力学窗口,使低表面能的含氟组分自发向涂层表层迁移并发生偏析,在保证树脂体系相容性的前提下降低了表面折射率,有效提升了光线透过率并赋予涂层优异的防污易清洁性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898012A_ABST
    Figure CN122898012A_ABST
Patent Text Reader

Abstract

The present application relates to the field of optical film technology, disclose the high efficiency light enhancement film of anti-reflection coating modification and its manufacturing method, including PET light enhancement film substrate and anti-reflection coating.The coating is made of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylmethyl formate, dipentaerythritol hexa-acrylate, hexafluorobisphenol A, perfluoropolyether urethane acrylate, N, N-diisopropyl ethylamine and initiator;Its manufacturing method includes that the homogeneous coating liquid is slit coated on the substrate, then is sent into different oven temperature zone and ultraviolet curing base station in turn and is cured in time sequence.By the cooperation of perfluoropolyether urethane acrylate and the preceding positive pressure leveling process, the fluorine component surface segregation is made to reduce the refractive index and promote the antifouling property;The inhibitor is removed by high temperature negative pressure, triggers cationic polymerization, the volume expansion of epoxy ring opening body offsets the volume shrinkage, and the adhesion of the coating is enhanced;And the internal stress accumulation is reduced, the macroscopic flatness of the film after winding is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical thin film technology, specifically to a high-efficiency brightness enhancement film modified with an anti-reflective coating and its manufacturing method. Background Technology

[0002] Brightness enhancement film is a core optical component in LCD backlight modules, primarily used to modulate the light emission angle to enhance the brightness of the display's front side. In practical applications, to reduce external light reflection loss on the flat surface of the brightness enhancement film and to give it scratch-resistant, easy-to-clean, and stain-resistant properties, an anti-reflective coating with both low refractive index and high hardness is typically applied to the flat surface of the film.

[0003] Currently, conventional antireflective coatings mainly employ free-radical UV-curable resin systems. While these systems exhibit rapid film formation during UV curing, they also suffer from significant volume shrinkage, resulting in severely insufficient adhesion between the cured coating and the PET substrate. This leads to easy peeling during subsequent processing or long-term use. Furthermore, free-radical polymerization is easily inhibited by oxygen in the air, resulting in incomplete micro-curing of the coating surface and reduced abrasion resistance. To reduce the refractive index and achieve anti-fouling and easy-to-clean properties, fluorinated oligomers are typically added to the system. However, traditional fluorinated oligomers have extremely poor compatibility with conventional acrylic resins. Insufficient compatibility easily leads to macroscopic phase separation, causing a significant increase in coating haze and severely impairing the optical transmittance of the brightness enhancement film.

[0004] To balance adhesion and reduce shrinkage, some studies have attempted to introduce free radical / cationic hybrid curing systems. However, in actual roll-to-roll continuous coating production, the viscosity of the system rises instantaneously due to the near-simultaneous triggering of free radical crosslinking and cationic polymerization during UV irradiation. This instantaneous gelation network tightly locks in material molecules, preventing the low-surface-energy fluorine components from effectively migrating and segregating to the outermost surface of the coating before film formation. Consequently, the final film fails to exhibit the expected low refractive index and high hydrophobic and antifouling effects. Furthermore, existing leveling and curing processes lack phased control over the dynamic film formation process. During the intertwining of solvent evaporation and crosslinking curing, a large amount of asymmetric internal stress often accumulates within the coating, making the film highly susceptible to warping and deformation, and even microcracks, after winding. This makes it difficult to meet the quality control requirements of high-precision, high-volume roll-to-roll industrial continuous production. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a high-efficiency brightness enhancement film modified with an anti-reflective coating and its manufacturing method. This solves the problems of poor adhesion and high haze caused by curing shrinkage and phase separation of components in existing brightness enhancement films, as well as the warping and cracking of the film during roll-to-roll continuous manufacturing caused by internal stress accumulation.

[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a high-efficiency brightness enhancement film modified with an anti-reflective coating, employing the following technical solution.

[0007] A high-efficiency brightness enhancement film modified with an anti-reflective coating includes a PET brightness enhancement film substrate and an anti-reflective coating coated on a flat surface of the substrate, wherein the anti-reflective coating is made of raw materials comprising the following parts by weight: 3,4-Epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate: 30-40 parts; Dipentaerythritol hexaacrylate: 35-45 parts; Bisphenol A hexafluorophosphate: 5-10 parts; Perfluoropolyether polyurethane acrylate: 10-25 parts; N,N-Diisopropylethylamine: 0.1–0.3 parts; 4-Acetoxyphenyl dimethylsulfonium hexafluoroantimonate: 0.5–2.0 parts; 5-Mixed photoinitiator: 2.0–5.0 parts. By adopting the above technical solution, the system possesses staged curing characteristics due to the construction of a free radical and cationic dual crosslinking network system using alicyclic epoxy resin and multifunctional acrylate, and the combination of sterically hindered N,N-diisopropylethylamine and the thermosensitive cationic initiator 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate.

[0008] Perfluoropolyether polyurethane acrylate, as a low-refractive-index and antifouling component, can migrate to the air-coating interface and accumulate before the resin matrix undergoes a large-scale crosslinking reaction. The hexafluoroisopropyl group in the hexafluorobisphenol A structure has a thermodynamic affinity with the perfluoropolyether segments, and the terminal phenolic hydroxyl groups interact polarly with the epoxy groups and polyurethane segments. This improves the compatibility between the perfluoropolyether polyurethane acrylate and the resin matrix, inhibits macroscopic phase separation, and results in an antireflective coating with low reflectivity, high light transmittance, low haze, and excellent surface antifouling and wear resistance.

[0009] Preferably, the mixed photoinitiator is composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0010] By adopting the above technical solution, the synergistic effect of the absorption wavelengths of the two photoinitiators in deep curing and surface curing is utilized to ensure the complete crosslinking of dipentaerythritol hexaacrylate during the free radical curing stage.

[0011] Preferably, the perfluoropolyether polyurethane acrylate is made from raw materials comprising the following parts by weight: 100 parts of hydroxyl-terminated perfluoropolyether with a number average molecular weight of 1500-2000; Isophorone diisocyanate: 22.8–30.4 parts; Anhydrous methyl ethyl ketone: 49.1–52.2 parts; Dibutyltin dilaurate: 0.06–0.07 parts; 2-Hydroxyethyl acrylate: 12.8–17.1 parts; p-hydroxyanisole: 0.14–0.15 parts.

[0012] Preferably, the perfluoropolyether polyurethane acrylate is prepared by the following steps: Under nitrogen protection, the terminal hydroxyl perfluoropolyether, isophorone diisocyanate, anhydrous methyl ethyl ketone and dibutyltin dilaurate are mixed and stirred at 65-75°C for 4-6 hours to obtain a urethane prepolymer intermediate solution with isocyanate groups at the end. The intermediate solution was cooled to 45–50°C, and the 2-hydroxyethyl acrylate was slowly added dropwise to the intermediate solution. After the addition was complete, the temperature was raised to 60–65°C and the reaction continued for 3–5 hours. The reaction was detected by infrared spectroscopy up to 2270 cm⁻¹. -1 The absorption peak of the isocyanate group at the point completely disappeared, and then the p-hydroxyanisole was added, followed by cooling and discharge.

[0013] By employing the above technical solution, a special resin comprising low surface energy perfluoropolyether segments, high cohesive energy urethane bonds, and terminal acrylate double bonds was synthesized stepwise. Under the catalysis of dibutyltin dilaurate, the hydroxyl-terminated perfluoropolyether undergoes a unilateral selective addition reaction with isophorone diisocyanate. Subsequently, 2-hydroxyethyl acrylate was slowly added dropwise under cooling conditions for end-capping, and the reaction endpoint was monitored in real time using infrared spectroscopy. The resin synthesized by this method has a well-defined structure; the perfluoropolyether segments provide low surface energy and low refractive index characteristics, while the terminal acrylate double bonds provide highly reactive free radical crosslinking sites.

[0014] Secondly, the present invention provides a method for manufacturing a high-efficiency brightness enhancement film modified with an anti-reflective coating, which adopts the following technical solution: A method for manufacturing a high-efficiency brightness enhancement film modified with an anti-reflective coating includes the following steps: 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, dipentaerythritol hexaacrylate, hexafluorobisphenol A, and a mixed solvent were mixed and heated to 40-45°C to dissolve. After cooling to 25°C, perfluoropolyether polyurethane acrylate, N,N-diisopropylethylamine, 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate, and a mixed photoinitiator were added. The mixture was stirred evenly and filtered to obtain a homogeneous coating solution. The homogeneous coating liquid is uniformly coated onto the flat surface of the PET gloss enhancement film substrate after online corona treatment using a roll-to-roll slit coating method to form a wet film. The wet film is sequentially sent into the pre-drying oven temperature zone, the subsequent high-temperature oven temperature zone, and the ultraviolet curing base station, and subjected to low-temperature positive pressure leveling, high-temperature negative pressure cationic curing, and free radical cross-linking curing, respectively, to obtain the final cured film. After the final cured film is stress-relieved by passing it through a cooling roller array, it is wound up under constant tension to obtain the finished high-efficiency brightening film.

[0015] By adopting the above technical solution, the time-curing process achieves staged control of the dynamic process of coating film formation, and regulates the kinetics of component migration and cross-linking curing. The reaction mechanism and process control process are as follows: During the low-temperature positive pressure leveling stage, trace amounts of protic acid released from the decomposition of 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate combine with N,N-diisopropylethylamine to form a complex salt, neutralizing the free protic acid. This chemical inhibition mechanism prevents the alicyclic epoxy resin from undergoing cross-linking and gelation reactions at low temperatures, maintaining the system in a low-viscosity state. This promotes the directional migration and enrichment of perfluoropolyether segments towards the air-coating interface, forming a gradient antireflective structure.

[0016] During the high-temperature, negative-pressure cationic curing stage, the complex salt dissociates, and the volatile N,N-diisopropylethylamine is vaporized and removed, shifting the complexation equilibrium towards the free protic acid. The free protic acid catalyzes the ring-opening polymerization of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbamate, constructing a three-dimensional cross-linked network structure, fixing the surface-enriched perfluoropolyether segments, and utilizing the volume expansion generated by the ring-opening polymerization to pre-establish the cross-linked scaffold.

[0017] During the free radical crosslinking curing and stress relaxation stages, the mixed photoinitiator triggers the free radical crosslinking polymerization of acrylate double bonds in the system. The volume shrinkage stress accompanying the free radical polymerization is dispersed and relaxed in the pre-established epoxy crosslinking network structure, reducing the residual internal stress inside the final coating.

[0018] Preferably, the mixed solvent is composed of propylene glycol methyl ether acetate and butanone in a mass ratio of 60:40 to 80:20.

[0019] By adopting the above technical solution, the reasonable ratio of high polarity and low polarity solvents ensures that all components in the coating solution are uniformly dispersed at the molecular level, preventing phase separation during storage.

[0020] Preferably, the treatment intensity of the online corona treatment is 15–25 W·min / m². 2 The roll-to-roll slit coating process operates at a speed of 15–30 m / min, and the dry film thickness corresponding to the wet film is controlled to be 2.0–4.0 μm.

[0021] By adopting the above technical solution, online corona treatment improves the surface tension of PET substrate, and controlling the speed of slit coating and dry film thickness ensures the coating uniformity of wet film and the stability of subsequent optical properties.

[0022] Preferably, the temperature gradient of the preceding oven temperature zone is set to 65-80°C, and the total residence time is 90-120 seconds; With the forced exhaust fan off, the internal temperature zone of the preceding oven is maintained at a positive pressure environment of +30 to +80 Pa.

[0023] By adopting the above technical solution, a stable and sufficient kinetic time window is provided for the migration and diffusion of perfluoropolyether segments and surface self-assembly. The positive pressure environment reduces the disturbance of airflow on the coating surface and ensures the leveling effect.

[0024] Preferably, the temperature of the subsequent high-temperature oven zone is set to 105-115°C, and the dwell time is 40-60 seconds; With the exhaust fan on, the internal temperature zone of the subsequent high-temperature oven is maintained at a negative pressure environment of -150 to -300 Pa to remove N,N-diisopropylethylamine.

[0025] By adopting the above technical solution, the negative pressure environment accelerates the mass transfer rate of sterically hindered amines from the inside of the coating to the gas phase, ensuring the complete triggering of the cationic polymerization reaction and the deep curing rate.

[0026] Preferably, the UV-curing base station has a nitrogen-protected environment, with the oxygen concentration controlled to be less than 500 ppm, and the irradiation energy density of the UV light source is 800–1200 mJ / cm². 2 ; The temperature of the cooling roller array is 20-25℃, and the constant tension during winding is 50-80 N / m.

[0027] By adopting the above technical solution, nitrogen protection reduces the inhibitory effect of oxygen on the free radical polymerization of acrylate and improves the surface hardness of the coating. Simultaneously, gentle cooling and constant tension were used to achieve a smooth release of residual internal stress in the substrate, preventing warping and deformation of the film after winding.

[0028] This invention provides a high-efficiency brightness enhancement film modified with an anti-reflective coating and its manufacturing method. It has the following beneficial effects: 1. This invention utilizes the positive pressure environment of the pre-curing oven in the combination of perfluoropolyether polyurethane acrylate and the pre-curing process to enable the low surface energy fluorinated components to spontaneously migrate to the coating surface and segregate before the large-scale construction of the crosslinking network by using a kinetic window. This reduces the surface refractive index while ensuring the compatibility of the resin system, effectively improves the light transmittance, and endows the coating with excellent anti-fouling and easy-to-clean properties.

[0029] 2. This invention constructs a free radical / cationic hybrid curing system by selecting 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and dipentaerythritol hexaacrylate, introduces hexafluorobisphenol A, and combines it with a subsequent high-temperature negative pressure environment to forcibly remove N,N-diisopropylethylamine to trigger cationic explosive gelation, thereby achieving the interwoven film formation of a dual curing network. The volume expansion of ring-opening polymerization effectively offsets the volume shrinkage caused by free radical polymerization, thereby improving the interfacial adhesion between the anti-reflective coating and the PET gloss enhancement film substrate.

[0030] 3. This invention achieves phased dynamic control of solvent removal, component migration and double crosslinking processes by adopting a process combination of pre-phase positive pressure leveling, post-phase high temperature negative pressure curing, ultraviolet free radical curing and stress relief by cooling rollers. This reduces the accumulation of internal stress during continuous production, ensures the macroscopic flatness of the film after constant tension winding, and solves the problem of warping deformation that easily occurs after film winding. Attached Figure Description

[0031] Figure 1 This is a graph showing the effect of the pre-heat treatment time on the F / C atomic ratio on the film surface in Test Example 1 of the present invention. Figure 2 This is a graph showing the effect of the pre-heat treatment time on the water contact angle and diiodomethane contact angle of the film surface in Test Example 1 of the present invention. Figure 3 This is a graph showing the effect of different heat treatment environments on the conversion rate of alicyclic epoxy groups in Test Example 2 of this invention. Figure 4 This is a comparison of the real-time infrared spectral behavior of the coating system under different heat treatment environments in Test Example 2 of this invention; Figure 5 The graphs show the spectral reflectance of the finished high-efficiency brightness enhancement films prepared in the embodiments and comparative examples of the present invention within the visible light wavelength range. Figure 6 This is a comparison chart of the total light transmittance and haze of the finished high-efficiency brightness enhancement films prepared in the embodiments and comparative examples of the present invention; Figure 7 This is a comparison diagram of the surface water contact angle changes before and after mechanical scratching and wear tests for embodiments and comparative examples of the present invention; Figure 8 This is a comparison diagram of the changes in the surface diiodomethane contact angle before and after the mechanical scratching and wear test between the embodiments and the comparative examples of the present invention; Figure 9 This is a comparison diagram of the warping height of the four corners of the finished high-efficiency brightness enhancement film prepared in the embodiments and comparative examples of the present invention. Detailed Implementation

[0032] The technical solutions of the present invention will be clearly and completely described below with reference to embodiments, comparative examples, and test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Preparation Examples 1-3: Preparation Example 1: This preparation example provides a method for preparing perfluoropolyether polyurethane acrylate, including the following steps: Step 1: 100 parts of hydroxyl-terminated perfluoropolyether with a number-average molecular weight of 1500 and 30.4 parts of isophorone diisocyanate were added to a reaction vessel. Then, 52.2 parts of anhydrous methyl ethyl ketone (MEK) were added as a co-solvent. 0.07 parts of dibutyltin dilaurate were added as a catalyst. Under nitrogen protection, the mixture was stirred at 65°C for 4 hours to obtain a urethane prepolymer intermediate solution with isocyanate-terminated groups.

[0034] Step 2: Lower the temperature of the intermediate solution in the reactor to 45°C, and slowly add 17.1 parts of 2-hydroxyethyl acrylate dropwise to the intermediate solution. After the addition is complete, raise the temperature to 60°C and continue the reaction for 3 hours. The reaction is then detected by infrared spectroscopy up to 2270 cm⁻¹. -1 The absorption peak of the isocyanate group at the point completely disappeared. Finally, 0.15 parts of p-hydroxyanisole were added as a polymerization inhibitor, and the mixture was cooled and discharged to obtain low molecular weight perfluoropolyether polyurethane acrylate resin.

[0035] Preparation Example 2: This preparation example provides a method for preparing perfluoropolyether polyurethane acrylate, including the following steps: Step 1: 100 parts of hydroxyl-terminated perfluoropolyether with a number-average molecular weight of 1800 and 25.3 parts of isophorone diisocyanate were added to a reaction vessel. Then, 50.1 parts of anhydrous methyl ethyl ketone (MEK) were added as a co-solvent. 0.06 parts of dibutyltin dilaurate were added as a catalyst. Under nitrogen protection, the mixture was stirred at 70°C for 5 hours to obtain a urethane prepolymer intermediate solution with isocyanate-terminated groups.

[0036] Step 2: Lower the temperature of the intermediate solution in the reactor to 48°C, and slowly add 14.2 parts of 2-hydroxyethyl acrylate dropwise to the intermediate solution. After the addition is complete, raise the temperature to 62°C and continue the reaction for 4 hours. The reaction is then monitored by infrared spectroscopy up to 2270 cm⁻¹. -1 The absorption peak of the isocyanate group at the point completely disappeared. Finally, 0.14 parts of p-hydroxyanisole were added as a polymerization inhibitor, and the mixture was cooled and discharged to obtain a medium molecular weight perfluoropolyether polyurethane acrylate resin.

[0037] Preparation Example 3: This preparation example provides a method for preparing perfluoropolyether polyurethane acrylate, including the following steps: Step 1: 100 parts of hydroxyl-terminated perfluoropolyether with a number-average molecular weight of 2000 and 22.8 parts of isophorone diisocyanate were added to a reaction vessel. Then, 49.1 parts of anhydrous methyl ethyl ketone (MEK) were added as a co-solvent. 0.06 parts of dibutyltin dilaurate were added as a catalyst. Under nitrogen protection, the mixture was stirred at 75°C for 6 hours to obtain a urethane prepolymer intermediate solution with isocyanate-terminated groups.

[0038] Step 2: Cool the intermediate solution in the reactor to 50°C, and slowly add 12.8 parts of 2-hydroxyethyl acrylate dropwise to the intermediate solution. After the addition is complete, raise the temperature to 65°C and continue the reaction for 5 hours. The reaction is then monitored by infrared spectroscopy up to 2270 cm⁻¹. -1 The absorption peak of the isocyanate group at the point completely disappeared. Finally, 0.14 parts of p-hydroxyanisole were added as a polymerization inhibitor, and the mixture was cooled and discharged to obtain high molecular weight perfluoropolyether polyurethane acrylate resin.

[0039] Examples 1-3: Example

[0040] This embodiment provides a method for manufacturing a high-efficiency brightness enhancement film modified with an anti-reflective coating, including the following steps: (1) Preparation of homogeneous coating solution: According to the mass fraction, add 40 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 45 parts of dipentaerythritol hexaacrylate, and 5 parts of hexafluorobisphenol A to the reactor. Add a mixed solvent composed of propylene glycol methyl ether acetate and butanone in a mass ratio of 60:40. Start stirring and heat to 40°C until the solid is completely dissolved.

[0041] The temperature was then lowered to 25°C, and 10 parts of the perfluoropolyether polyurethane acrylate prepared in Preparation Example 1, 0.1 parts of N,N-diisopropylethylamine, 0.5 parts of 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate, and 2.0 parts of a mixed photoinitiator composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 3:1 were added. The solid content of the system was adjusted to 40% by adjusting the amount of mixed solvent. After filtration through a 1.0 μm filter, a homogeneous coating solution was obtained.

[0042] (2) Roll-to-roll slot coating: Using a roll-to-roll slot coating machine, the flat surface of the PET gloss enhancement film substrate is subjected to online corona treatment at a speed of 30 m / min and a treatment intensity of 15 W·min / m. 2 The homogeneous coating liquid obtained in step (1) is uniformly coated on the flat surface of the substrate after corona treatment. The pressure of the feed pump is adjusted to obtain a wet film with a dry film thickness of 2.0 μm as expected.

[0043] (3) Time-series curing process: First, the wet film obtained in step (2) is sent into the temperature zone of the pre-drying oven. The temperature gradient is set to 65℃-70℃-75℃, and the total residence time is 90s. The forced exhaust is turned off to maintain a positive pressure environment of +30Pa inside the temperature zone of the pre-drying oven, so as to induce surface segregation of components and perform low-temperature positive pressure leveling.

[0044] Next, the film treated in the previous oven temperature zone is sent to the subsequent high-temperature oven temperature zone, where the temperature is set to 105℃ and the residence time is 40s. The maximum exhaust volume is turned on to maintain a negative pressure environment of -150Pa inside the subsequent high-temperature oven temperature zone, forcibly removing N,N-diisopropylethylamine, triggering cationic explosive gelation, and performing high-temperature negative pressure cationic curing.

[0045] Subsequently, the film, after being treated in a high-temperature oven, was placed in a UV curing station and irradiated with a UV light source under a nitrogen-protected environment (oxygen concentration less than 500 ppm) to perform free radical cross-linking curing. The irradiation energy density was 800 mJ / cm². 2 The final cured film is obtained.

[0046] (4) Cooling and winding: After stress relief by passing the final cured film obtained in step (3) through a cooling roller array at a temperature of 20°C, it is wound up under a constant tension of 50 N / m to obtain the finished high-efficiency brightening film. Example

[0047] This embodiment provides a method for manufacturing a high-efficiency brightness enhancement film modified with an anti-reflective coating, including the following steps: (1) Preparation of homogeneous coating solution: According to the mass fraction, add 35 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 42 parts of dipentaerythritol hexaacrylate, 8 parts of hexafluorobisphenol A, and a mixed solvent composed of propylene glycol methyl ether acetate and butanone in a mass ratio of 70:30. Start stirring and heat to 43°C until the solid is completely dissolved.

[0048] The temperature was then lowered to 25°C, and 15 parts of the perfluoropolyether polyurethane acrylate prepared in Preparation Example 2, 0.2 parts of N,N-diisopropylethylamine, 1.0 part of 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate, and 3.0 parts of a mixed photoinitiator composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 3:1 were added. The solid content of the system was adjusted to 35% by adjusting the amount of mixed solvent. After filtration through a 1.5 μm filter, a homogeneous coating solution was obtained.

[0049] (2) Roll-to-roll slot coating: Using a roll-to-roll slot coating machine, the flat surface of the PET gloss enhancement film substrate is subjected to online corona treatment at a speed of 22 m / min and a treatment intensity of 20 W·min / m. 2 The homogeneous coating liquid obtained in step (1) is uniformly coated on the flat surface of the substrate after corona treatment. The pressure of the feed pump is adjusted to obtain a wet film with a dry film thickness of 3.0 μm as expected.

[0050] (3) Time-sequence curing treatment: First, the wet film obtained in step (2) is sent into the temperature zone of the pre-drying oven. The temperature gradient is set to 65℃-75℃-80℃, and the total residence time is 105s. The forced exhaust is turned off to maintain a positive pressure environment of +50Pa inside the temperature zone of the pre-drying oven, so as to induce surface segregation of components and perform low-temperature positive pressure leveling.

[0051] Next, the film treated in the previous oven temperature zone is sent to the subsequent high-temperature oven temperature zone, where the temperature is set to 110℃ and the residence time is 50s. The maximum exhaust volume is turned on to maintain a negative pressure environment of -200Pa inside the subsequent high-temperature oven temperature zone, forcibly removing N,N-diisopropylethylamine, triggering cationic burst gelation, and performing high-temperature negative pressure cationic curing.

[0052] Subsequently, the film, after being treated in a high-temperature oven, was placed in a UV curing station and irradiated with a UV light source under a nitrogen-protected environment (oxygen concentration less than 500 ppm) to perform free radical cross-linking curing. The irradiation energy density was 1000 mJ / cm². 2 The final cured film is obtained.

[0053] (4) Cooling and winding: After stress relief by passing the final cured film obtained in step (3) through a cooling roller array at a temperature of 23°C, it is wound up under a constant tension of 65 N / m to obtain the finished high-efficiency brightening film. Example

[0054] This embodiment provides a method for manufacturing a high-efficiency brightness enhancement film modified with an anti-reflective coating, including the following steps: (1) Preparation of homogeneous coating solution: According to the mass fraction, add 30 parts of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 35 parts of dipentaerythritol hexaacrylate, 10 parts of hexafluorobisphenol A to the reaction vessel, add a mixed solvent composed of propylene glycol methyl ether acetate and butanone in a mass ratio of 80:20, start stirring and heat to 45°C until the solid is completely dissolved.

[0055] The temperature was then lowered to 25°C, and 25 parts of the perfluoropolyether polyurethane acrylate prepared in Preparation Example 3, 0.3 parts of N,N-diisopropylethylamine, 2.0 parts of 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate, and 5.0 parts of a mixed photoinitiator composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 3:1 were added. The solid content of the system was adjusted to 30% by adjusting the amount of mixed solvent. After filtration through a 2.0 μm filter, a homogeneous coating solution was obtained.

[0056] (2) Roll-to-roll slot coating: Using a roll-to-roll slot coating machine, the flat surface of the PET gloss enhancement film substrate is subjected to online corona treatment at a speed of 15 m / min and a treatment intensity of 25 W·min / m. 2 The homogeneous coating liquid obtained in step (1) is uniformly coated on the flat surface of the substrate after corona treatment. The pressure of the feed pump is adjusted to obtain a wet film with a dry film thickness of 4.0 μm as expected.

[0057] (3) Time-sequence curing treatment: First, the wet film obtained in step (2) is sent into the temperature zone of the pre-drying oven. The temperature gradient is set to 70℃-75℃-80℃, and the total residence time is 120s. The forced exhaust is turned off to maintain a positive pressure environment of +80Pa inside the temperature zone of the pre-drying oven, so as to induce surface segregation of components and perform low-temperature positive pressure leveling.

[0058] Next, the film treated in the previous oven temperature zone is sent to the subsequent high-temperature oven temperature zone, where the temperature is set to 115℃ and the residence time is 60s. The maximum exhaust volume is turned on to maintain a negative pressure environment of -300Pa inside the subsequent high-temperature oven temperature zone, forcibly removing N,N-diisopropylethylamine, triggering cationic burst gelation, and performing high-temperature negative pressure cationic curing.

[0059] Subsequently, the film, after being treated in a high-temperature oven, was placed in a UV curing station and irradiated with a UV light source under a nitrogen-protected environment (oxygen concentration less than 500 ppm) to perform free radical cross-linking curing. The irradiation energy density was 1200 mJ / cm². 2 The final cured film is obtained.

[0060] (4) Cooling and winding: After stress relief by passing the final cured film obtained in step (3) through a cooling roller array at a temperature of 25°C, it is wound up under a constant tension of 80 N / m to obtain the finished high-efficiency brightening film.

[0061] Comparative Examples 1-5: Comparative Example 1: Compared with Example 2, the difference is that N,N-diisopropylethylamine in the formulation of the homogeneous coating solution in step (1) was removed, while the other steps and components are the same.

[0062] Comparative Example 2: Compared with Example 2, the difference is that in the preparation of the homogeneous coating solution in step (1), the sterically hindered N,N-diisopropylethylamine is replaced with the conventional low-sterically hindered amine N,N-dimethylethanolamine in equimolar amounts, while the other steps and components are the same.

[0063] Comparative Example 3: Compared with Example 2, the difference is that in the sequential curing process in step (3), the maximum exhaust volume is not turned on when the film is sent into the temperature zone (110°C) of the subsequent high-temperature oven, and the same +50Pa positive pressure environment as the previous oven is maintained throughout the process. The other steps and components are the same.

[0064] Comparative Example 4: Compared with Example 2, the difference is that in the preparation of the homogeneous coating solution in step (1), hexafluorobisphenol A was directly removed. At the same time, in order to make up for the solid content, the amount of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbamate was increased to 43 parts. The remaining steps and components are the same.

[0065] Comparative Example 5: Compared with Example 2, the difference is that after the roll-to-roll slit coating in step (2) is completed, the curing sequence of step (3) is changed: the obtained wet film is sent to the conventional 85°C oven temperature zone for 2 minutes to evaporate the solvent, then sent to the UV curing base station for UV free radical curing, and finally sent to the 110°C oven temperature zone for thermal cationic curing (the traditional process with the curing sequence reversed), and the other components are the same.

[0066] Test Examples 1-5: Test Example 1: Kinetic Tracking of Surface Self-Assembly Segregation of Perfluoropolyether Segments Experimental steps (1) The temperature gradient conditions of the pre-heating oven temperature zone in step (3) of Example 2 (i.e., continuous linear heating process of 65℃-75℃-80℃) were simulated using a coating sample making machine. The wet film sample obtained by slit coating in step (2) was placed in a leveling heat treatment chamber with pressure control. By adjusting the running speed of the conveyor belt or the dwell time of a single piece, film samples with pre-heat treatment times of 0s, 20s, 40s, 60s, 80s and 105s were respectively cut. The entire slicing and collection process was carried out in a positive pressure leveling environment of +50Pa inside the chamber.

[0067] (2) The collected film samples at each time point were immediately immersed in liquid nitrogen for cryogenic quenching to rapidly freeze the molecular motion state at different stages and terminate further segregation of the perfluoropolyether chain segments. After quenching, the samples were transferred to a vacuum drying oven and allowed to naturally warm up and dehydrate at room temperature (25°C) to ensure that no condensate residue remained on the surface.

[0068] (3) Using a contact angle measuring instrument (DSA100), the static water contact angle (WCA) and diiodomethane contact angle of each quenched sample surface were tested by the droplet method under a standard laboratory environment with a temperature of 25℃ and a relative humidity of 50%. Five different areas of each sample surface were randomly selected for droplet addition and optical imaging analysis. After removing outliers, the arithmetic mean was taken.

[0069] (4) An X-ray photoelectron spectrometer (XPS, K-Alpha type) was used with monochromatic AlKα rays (1486.6 eV) as the excitation source, and the vacuum level in the analysis chamber was maintained at 5 × 10⁻⁶. -9 Below mbar. To accurately capture compositional variations within the nanoscale thin layer on the surface, the take-off angle for photoelectron spectroscopy analysis was set to 90°, corresponding to an effective detection depth of approximately 10 nm. First, a full-spectrum scan of each sample surface was performed to determine the elemental composition. Then, high-resolution narrow-spectrum scans were conducted on the F1s and C1s characteristic peaks. Using the instrument's built-in software, the integrated area of ​​the high-resolution peaks was calculated. After introducing an atomic sensitivity factor correction, the absolute molar percentage content of F and C atoms on the outermost surface of the coating was calculated, thus determining the surface F / C atomic ratio.

[0070] Experimental data: Table 1. Effect of pre-treatment time on surface elements and contact angle of film in Example 2

[0071] Based on the data in Table 1, Figure 1 as well as Figure 2 The test results show that as the pre-heat treatment time increases, the chemical composition and surface wettability of the film surface change synchronously.

[0072] Depend on Figure 1 It can be seen that the F / C atomic ratio on the outermost surface of the coating increases rapidly from 0s to 60s, rising from an initial 0.0177 to 0.1701; after 80s, the growth slows down, reaching 0.2304 at 105s. Figure 2 As can be seen, with the heat treatment time increasing from 0 s to 105 s, the water contact angle on the film surface increased from 71.8° to 111.6°, and the diiodomethane contact angle increased from 40.9° to 72.9°. The water contact angle reached 97.5° at 40 s and essentially stabilized at 105 s. The enrichment trend of the microscopic chemical components is consistent with the test results of the macroscopic contact angle.

[0073] The above results are consistent with the reaction and leveling mechanism of this invention. By introducing sterically hindered N,N-diisopropylethylamine (DIPEA) into the formulation system, DIPEA combines with the protonic acid released by the cationic thermosensitive initiator to form a reversible salt within the pre-drying oven temperature range (65℃-75℃-80℃). This mechanism inhibits the crosslinking and gelation reaction of the 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbamate matrix at low temperatures, thus maintaining a low viscosity of the system within this temperature range.

[0074] During this stage, the perfluoropolyether (PFPE) segments in the perfluoropolyether polyurethane acrylate resin overcome migration resistance and migrate directionally to the air-coating interface and accumulate and distribute themselves under the thermodynamic drive of reducing surface free energy. Figure 1 and Figure 2 The data in the 80s to 105s range tends to saturate, indicating that the perfluoropolyether segment arrangement density in the outermost layer of the coating (within a detection depth of approximately 10nm) is close to equilibrium. This kinetic tracking result demonstrates that by controlling the preceding gradient temperature range, positive pressure environment, and leveling time, a highly fluorine-enriched, low-refractive-index antireflective structure can be formed on the coating surface before the radical and cationic networks are fully cross-linked and cured.

[0075] Test Example 2: Verification of the thermal desorption protection behavior of sterically hindered amines on cationic initiators Experimental steps: (1) A real-time Fourier transform infrared spectrometer (RT-FTIR) equipped with an in-situ micro heating drying cavity and a pressure regulation system was used, and the infrared test mode was adjusted to total reflection (ATR) mode.

[0076] (2) Take the homogeneous coating liquid prepared in Example 2 and coat it evenly on the surface of the infrared test crystal. Control the initial thickness of the wet film so that the absorption intensity of the infrared detection signal is within the linear response range.

[0077] (3) Locking alicyclic epoxy groups at a wavenumber of 790 cm⁻¹ -1 Nearby characteristic absorption peaks were selected as monitoring targets, while the characteristic absorption peak of ester groups that do not participate in the chemical reaction (wavenumber 1730 cm⁻¹) was also selected. -1 The peaks near the epoxide group were used as internal standards. The real-time conversion rate of the epoxide group was obtained by calculating the percentage reduction in the area of ​​the characteristic absorption peak relative to the initial unreacted state peak area at a specific reaction time.

[0078] (4) Set three different heat treatment comparison environments, start the continuous scanning mode of infrared spectroscopy, and set the time resolution to 1s: Environment 1 (simulated low temperature hibernation stage): The temperature of the measuring chamber is kept constant at 75℃, and the internal positive pressure environment is maintained at +50Pa for 150s.

[0079] Environment 2 (comparison to the high temperature stage without negative pressure): The temperature of the measuring chamber is rapidly increased from 25℃ and kept constant at 110℃. The positive pressure environment of +50Pa is maintained inside the chamber throughout the process. Forced ventilation is not turned on, and continuous monitoring is performed for 150s.

[0080] Environment 3 (Simulated standard process high temperature stage): The temperature of the measuring chamber is rapidly increased from 25℃ and kept constant at 110℃. At the same time, the maximum exhaust fan is turned on, so that the inside of the chamber is instantly switched and maintained at a negative pressure environment of -200Pa, and continuously monitored for 150s.

[0081] Experimental data: Table 2. Effect of different heat treatment conditions on the conversion rate of alicyclic epoxy groups

[0082] Based on the data in Table 2, Figure 3 and Figure 4 The test results show that the crosslinking and curing kinetics of alicyclic epoxy groups in the coating system differ significantly under different temperature and pressure control environments.

[0083] Under ambient conditions (75℃, +50Pa positive pressure), the conversion rate of the epoxy groups was extremely low, reaching only 2.2% after 150 s of reaction. This indicates that in the low-temperature pre-reaction phase of the formulation, the trace protic acid generated by 4-acetoxyphenyl dimethylsulfonium hexafluoroantimonate is neutralized by the sterically hindered amine N,N-diisopropylethylamine (DIPEA) within the system, forming a reversible dormant salt with acid-base complexation. This chemical inhibition mechanism manifests macroscopically as reaction stagnation, providing a low-viscosity segregation time window without gel resistance for the perfluoropolyether segments.

[0084] Under environmental conditions II (110℃, +50Pa positive pressure, no negative pressure exhaust), although the temperature increase caused the initiator to decompose and the dormant salt to partially thermally dissociate, the DIPEA released after deprotection could not effectively evaporate and escape from the coating interior and surface through gas mass transfer due to the positive pressure maintained in the chamber and the lack of forced air convection. Consequently, the acid-base balance in the reaction system was difficult to shift to the right. Therefore, the concentration of free protic acid was limited, resulting in a slow curing rate of the epoxy groups. At 150s, the matrix conversion rate only reached 30.5%, failing to form a high-density cross-linked scaffold network.

[0085] Under environmental conditions (110℃, -200Pa negative pressure), the curing kinetics of the epoxy groups changed. Within 60 seconds of entering this environment, the epoxy conversion rate increased from 0.0% to 52.8%, reached 82.6% at 90 seconds, and finally reached a nearly fully cured state of 93.4% at 150 seconds. This is because the high vacuum negative pressure environment disrupted the gas-liquid balance, forcibly causing the DIPEA generated by thermal decomposition protection to vaporize and rapidly leave the system, completely shifting the complexation equilibrium to the right. This instantaneously released a high concentration of active hexafluoroantimony protonic acid within the coating, thereby triggering an explosive cationic ring-opening polymerization reaction of the alicyclic epoxy resin.

[0086] Test Example 3: Optical Performance and Anti-reflection Effect Test Experimental steps: (1) The finished high-efficiency brightness enhancement films prepared in Examples 1-3, Comparative Example 1 and Comparative Example 4 were cut into 50mm×50mm square test samples. Lamination of black opaque high-absorption tape was uniformly attached to the uncoated side of each sample (i.e. the prism side of the PET substrate) to completely eliminate the physical interference of multiple reflections from the back of the substrate and the prism structure on the optical test results of the coating surface.

[0087] (2) Using a spectrophotometer (UV-2600 model, equipped with integrating sphere test accessory), baseline calibration of the dual optical path was performed using a standard alumina white plate before the test. The sample with black tape was fixed at the specular reflection test window of the integrating sphere, the incident angle was set to 8°, and the spectral reflectance curve of each sample surface was obtained by scanning in the visible light wavelength range of 380nm to 780nm. The lowest reflectance value was extracted from the data curve.

[0088] (3) Using a haze meter (Haze-gardi type), according to the ASTM D1003 standard test method for transmittance and haze, the original finished film sample without black tape was subjected to vertical incident measurement, and the absolute percentage values ​​of total light transmittance and haze were directly read.

[0089] (4) In order to eliminate the measurement error caused by the slight fluctuation of longitudinal and transverse thickness during roll-to-roll coating, five test points were randomly changed in different areas of the surface of each sample for data collection. After removing the abnormal response values ​​at the edges, the arithmetic mean of the remaining measurement results was taken as the final optical performance characterization parameter of the sample.

[0090] Experimental data: Table 3. Comparison of optical performance parameters between the examples and comparative examples

[0091] Based on the data in Table 3, Figure 5 as well as Figure 6The test results showed that the brightness enhancement films prepared in Examples 1-3 were superior to those in Comparative Examples 1 and 4 in all optical properties. Among all groups, the scheme in Example 2 showed the best optical adjustment effect, with its minimum reflectance reduced to 0.41%, total light transmittance increased to 94.62%, and haze of only 0.35%.

[0092] The differences in optical properties among the groups are directly related to the microscopic changes within the system. Comparative Example 1 did not include the sterically hindered amine N,N-diisopropylethylamine (DIPEA) in its formulation, resulting in a lack of a preceding low-temperature dormancy period. This caused the epoxy resin matrix to undergo premature chemical crosslinking and gelation in the preceding oven step (3). This prematurely constructed rigid network limited the diffusion ability of the fluorinated segments in the perfluoropolyether polyurethane acrylate resin, preventing them from fully migrating and accumulating at the air-coating interface during the leveling window. Figure 5 The data shows that the minimum reflectivity of Comparative Example 1 increased from 0.41% in Example 2 to 1.45%, indicating that the surface layer lacks an ordered arrangement of high-density fluorine elements and fails to form the expected low-refractive-index anti-reflective layer structure.

[0093] Comparative Example 4 removed hexafluorobisphenol A (6F-BPA) from its formulation. Due to the poor thermodynamic compatibility between the non-polar characteristics of the perfluoropolyether polyurethane acrylate resin and the highly polar epoxy / acrylate matrix, and the lack of hexafluorobisphenol A, which provides a polar transition, to act as a compatibilizer, macroscopic phase separation occurred during solvent evaporation. Figure 6 The data comparison shows that the haze of Comparative Example 4 increased sharply from 0.35% in Example 2 to 6.45%, while the total light transmittance decreased from 94.62% to 87.54%. This indicates that the appearance of the large-scale heterogeneous structure inside caused significant visible light scattering, resulting in macroscopic whitening of the film.

[0094] In conclusion, Figure 5 and Figure 6 The comparative results show that by controlling the leveling dynamics window with DIPEA and maintaining the compatibility and stability of the system with 6F-BPA, phase separation can be effectively suppressed, and a low-refractive-index gradient anti-reflection structure can be formed on the coating surface before crosslinking and locking, thus achieving the synergy of high light transmittance, low haze and low reflection of the brightness enhancement film.

[0095] Test Example 4: Surface Anti-fouling, Anti-scratch, and Wear Resistance Test Experimental steps: (1) The finished high-efficiency brightness enhancement film samples prepared in Examples 1-3, Comparative Examples 1, 2 and 3 were cut and fixed on a horizontal rigid test platform, keeping the coating surface flat and wrinkle-free. Under an environment of 25°C and 50% relative humidity, the initial static water contact angle and initial diiodomethane contact angle of the coating surface of each group of samples were tested using a contact angle measuring instrument (DSA100).

[0096] (2) Transfer the sample to be tested onto the test platform of the friction and wear resistance tester (MCJ-01A type). Select 0000# standard steel wool as the friction medium and fix it under the wear resistance test head with an area of ​​1cm×1cm. Adjust the counterweight of the test head so that the mechanical load acting on the surface of the thin film coating reaches 1.0kg / cm. 2 .

[0097] (3) Start the wear and friction tester, set the unidirectional stroke to 50mm, the test speed to 60 reciprocating cycles / min, and conduct 500 reciprocating mechanical scratch wear tests on the surface of each group of thin film samples.

[0098] (4) After the friction test is completed, remove the sample and use low-pressure dry degreasing compressed air to blow away the coating surface and remove the trace debris generated by the scratch. Fix the sample on the contact angle measuring instrument again, and measure the static water contact angle and diiodomethane contact angle after wear in the wear area rubbed with steel wool using the same method. Collect data from 5 different points for each sample, and take the arithmetic mean as the final evaluation data.

[0099] Experimental data: Table 4. Comparison of surface contact angle changes before and after wear resistance friction in the examples and comparative examples

[0100] Based on the data in Table 4, Figure 7 as well as Figure 8 The test results showed that the coatings prepared in Examples 1-3 maintained a high surface contact angle after 500 cycles of steel wool rubbing. Taking Example 2 as an example, the surface water contact angle and diiodomethane contact angle after the abrasion test were 108.4° and 70.2°, respectively, with relatively small changes compared to the initial values. In contrast, the contact angle retention rates of Comparative Examples 1-3 all decreased after mechanical scratching.

[0101] The differences in wear resistance among the groups stem from varying degrees of control over the enrichment state and cross-linking network structure of the coating surface. Comparative Example 1, which did not contain DIPEA, experienced cross-linking and gelation of the epoxy resin matrix during the low-temperature leveling stage due to the lack of sterically hindered amine's chemical inhibition of protic acids. This pre-constructed network structure limited the migration of perfluoropolyether segments to the air-coating interface. Figure 7 and Figure 8The data shows that the initial water contact angle and diiodomethane contact angle of Comparative Example 1 were only 85.4° and 50.2°, respectively, indicating that an effective high-fluorine-content, low-surface-energy layer was not formed on the coating surface.

[0102] Although the initial contact angles of Comparative Example 2 were similar to those of Example 2, after the friction test, its water contact angle decreased from 110.8° to 65.4°, and its diiodomethane contact angle decreased from 72.1° to 35.2°. This is because Comparative Example 2 used DMEA, a conventional amine with less steric hindrance, instead of DIPEA. The salt formed by this low-hindrance amine and protic acid is relatively stable and cannot undergo effective dissociation under heat treatment at 110°C, limiting the release of free protic acid. This resulted in the alicyclic epoxy resin in the underlying layer failing to undergo sufficient cationic ring-opening polymerization. Because the underlying matrix did not form a high-density chemical cross-linked network, the fluorinated segments enriched on the surface lacked sufficient mechanical support and physical anchoring, making them easily lost due to matrix damage during steel wool scraping.

[0103] The initial contact angle of Comparative Example 3 met expectations, but after the wear test, the water contact angle and the diiodomethane contact angle decreased to 82.6° and 48.3°, respectively. This indicates that in the subsequent high-temperature heat treatment stage, if the negative pressure exhaust is not activated and a positive pressure environment is maintained, the DIPEA decomposed within the system cannot efficiently evaporate and escape, preventing the complexation equilibrium from shifting to the right. Insufficient free protic acid concentration reduces the curing rate and overall crosslinking density of the epoxy network. Under external frictional shear forces, this low-crosslinking network structure is prone to physical cohesive failure and cannot permanently lock in the fluorinated macromolecules on the surface.

[0104] In summary, Table 4 and Figure 7 , Figure 8 Comparative data show that there is a synergistic effect between the chemical structure of the sterically hindered amine and the subsequent high-temperature negative pressure curing process. By breaking the complexation equilibrium and forcibly removing DIPEA through high temperature combined with negative pressure suction, the alicyclic epoxy resin can be fully cross-linked to construct a three-dimensional network with mechanical strength, thereby firmly anchoring the self-assembled perfluoropolyether segments enriched on the surface and achieving long-lasting surface antifouling and abrasion resistance.

[0105] Test Example 5: Testing of Internal Stress and Anti-curling Physical Properties of Thin Films Experimental steps: (1) The finished high-efficiency brightening film samples prepared in Examples 1-3 and Comparative Example 5 were placed in a standard constant temperature and humidity environment room with a temperature of 23°C and a relative humidity of 50% for 24 hours to eliminate the influence of environmental temperature and humidity fluctuations on the mechanical deformation state of the film.

[0106] (2) Using a cross-cut adhesion tester (compliant with ASTM D3359), 10×10 squares with a spacing of 1 mm were vertically cut across the coating surface of each sample, with the cuts extending to the PET substrate surface. After gently removing debris from the marked areas with a soft brush, the standard test tape (3M 610 type) was firmly attached to the marked areas, and a rubber scraper was used to press it back and forth to remove air bubbles and ensure close contact between the tape and the coating. Within 90 seconds of attachment, one end of the tape was pulled and quickly peeled off at an angle of approximately 180°. The area of ​​coating peeling off in the marked areas was observed using a magnifying glass, and the adhesion level was evaluated.

[0107] (3) The flexibility of the coating was tested using a cylindrical shaft bending tester (compliant with GB / T6742 standard). Each group of film samples was cut into strips of 20mm × 100mm. The coated side was placed tightly against steel cylindrical shafts of different diameters (2.0mm, 3.0mm, 4.0mm, 6.0mm, 8.0mm, 10.0mm) for a 180° bending test. After bending, the coating surface at the bending point was observed using a 10x magnifying glass, and the minimum cylindrical shaft diameter corresponding to the point when the coating began to show microcracks or peeling was recorded.

[0108] (4) Each group of film samples was precisely cut into 100mm×100mm square sheets and placed flat on a high-flatness precision marble platform. After standing for 12 hours in a constant temperature and humidity environment, the vertical height of the four warp corners of the square film from the marble platform was measured using a digital depth gauge or feeler gauge. Three sheets were tested for each sample, and the arithmetic mean of the 12 warp height data was calculated as the finished warp height of the sample.

[0109] Experimental data: Table 5. Comparison of physical and mechanical properties and anti-curling properties between the examples and comparative examples.

[0110] Based on the data in Table 5 and Figure 9 According to the test results, the finished films prepared in Examples 1 to 3 are superior to Comparative Example 5 in terms of cross-cut adhesion, bending flexibility, and resistance to warping deformation.

[0111] Examples 1-3 all achieved a 5B level of adhesion across the 100-grid surface, with the minimum flexural diameter remaining between 2.0 mm and 3.0 mm, and the corner warpage height of the finished product controlled within 1.2 mm. Among them, Example 2 showed the most stable overall mechanical deformation control, with a warpage height of only 0.5 mm. In contrast, Comparative Example 5, which used the reverse curing sequence process, showed a decrease in adhesion to a 2B level, an increase in the minimum flexural diameter to 8.0 mm, and an increase in corner warpage height to 14.3 mm, with the film exhibiting obvious macroscopic curling.

[0112] The differences in the aforementioned physical and mechanical properties stem from the mechanism by which the timing of different crosslinking network constructions regulates the residual stress within the system. In the curing processes used in Examples 1-3, the wet film first undergoes DIPEA removal under negative pressure in the high-temperature zone of an oven, initiating a cationic ring-opening polymerization reaction of the alicyclic epoxy resin matrix. This process pre-constructs a three-dimensional epoxy crosslinking network framework before the film enters the UV curing stage. When the film subsequently enters the UV curing stage, dipentaerythritol hexaacrylate (DPHA) undergoes free radical polymerization, and the volume shrinkage stress accompanying the crosslinking and curing of the acrylate double bonds can be dispersed and relaxed within the already formed epoxy resin framework structure, thereby reducing the residual internal stress within the final coating. In terms of macroscopic performance, this manifests as good interfacial adhesion between the coating and the PET substrate, no stress concentration cracking during bending, and the finished film maintaining flatness over a large area.

[0113] Comparative Example 5 altered the curing sequence, first performing UV irradiation for free radical curing, and finally high-temperature cationic curing. During the UV irradiation stage, the high-functionality acrylate monomers rapidly polymerized. At this stage, the epoxy resin monomers and hexafluorobisphenol A in the system did not participate in the chemical reaction, existing only as free media. The acrylate network underwent volume shrinkage in this state, generating high residual stress within the coating.

[0114] Subsequently, during the high-temperature drying stage, the epoxy monomers trapped within the shrinkage network are forced to undergo ring-opening polymerization, resulting in secondary volume shrinkage. Internal stress cannot be relaxed and accumulates further. This high residual stress weakens the interfacial shear strength between the coating and the PET substrate, leading to peeling during cross-cut adhesion testing and deterioration of adhesion. Simultaneously, the internal stress increases the coating's brittleness, reducing its bending resistance. Because the shrinkage internal stress on the coating side is significantly greater than that on the PET substrate side, the composite film ultimately curls towards the coating side, increasing the warpage height.

[0115] The test results quantitatively confirm that the specific time-sequence curing process, which first constructs the matrix framework through thermal cationic reaction and then absorbs shrinkage stress through ultraviolet free radical reaction, is the process condition for reducing residual stress in the coating, improving adhesion, and inhibiting film deformation.

Claims

1. A high-efficiency brightness enhancement film modified with an anti-reflective coating, comprising a PET brightness enhancement film substrate and a coating applied to the substrate. An anti-reflective coating on a flat surface of a substrate, characterized in that, The anti-reflective coating consists of components comprising the following weight Made from the following ingredients: 3,4-Epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate: 30-40 parts; Dipentaerythritol hexaacrylate: 35-45 parts; Bisphenol A hexafluorophosphate: 5-10 parts; Perfluoropolyether polyurethane acrylate: 10-25 parts; N,N-Diisopropylethylamine: 0.1–0.3 parts; 4-Acetoxyphenyl dimethylsulfonium hexafluoroantimonate: 0.5–2.0 parts; Mixed photoinitiator: 2.0–5.0 parts.

2. The high-efficiency brightness enhancement film modified with an anti-reflective coating according to claim 1, characterized in that, The mixed photoinitiator is composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenyl ketone. The composition is based on phosphine oxide.

3. The high-efficiency brightness enhancement film modified with an anti-reflective coating according to claim 1, characterized in that, The perfluoropolyether polyurethane acrylate is made from raw materials comprising the following parts by weight: 100 parts of hydroxyl-terminated perfluoropolyether with a number average molecular weight of 1500-2000; Isophorone diisocyanate: 22.8–30.4 parts; Anhydrous methyl ethyl ketone: 49.1–52.2 parts; Dibutyltin dilaurate: 0.06–0.07 parts; 2-Hydroxyethyl acrylate: 12.8–17.1 parts; p-Hydroxyanisole: 0.14–0.15 parts.

4. The high-efficiency brightness enhancement film modified with an anti-reflective coating according to claim 3, characterized in that, The perfluoropolyether polyurethane acrylate is prepared by the following steps: Under nitrogen protection, the terminal hydroxyl perfluoropolyether, isophorone diisocyanate, and anhydrous butane were... The ketone was mixed with dibutyltin dilaurate and stirred at 65-75°C for 4-6 hours to obtain a urethane prepolymer intermediate solution with isocyanate groups at the end. The intermediate solution was cooled to 45–50°C, and the [substance name] was slowly added dropwise to the intermediate solution. 2-Hydroxyethyl acrylate was added dropwise, and the temperature was raised to 60–65°C to continue the reaction for 3–5 hours. The reaction was then monitored by infrared spectroscopy. The isocyanate group absorption peak at 2270 cm⁻¹ completely disappeared upon spectral detection, and then the p-hydroxyl group was added. Anisole, cooled and discharged.

5. A method for manufacturing a high-efficiency brightness enhancement film modified with an anti-reflective coating, characterized in that, Used for preparing rights The high-efficiency brightness enhancement film modified with the anti-reflective coating according to any one of claims 1-4 includes the following steps: 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, dipentaerythritol hexaacrylate, Hexafluorobisphenol A is mixed with a mixed solvent, heated to 40–45°C to dissolve, and then cooled to 25°C before adding perfluorinated compounds. Polyether polyurethane acrylate, N,N-diisopropylethylamine, 4-acetoxyphenyl dimethylsulfonium hexafluoroantimony Salt and mixed photoinitiator are stirred evenly and filtered to obtain a homogeneous coating solution; The homogeneous coating liquid is uniformly applied to the area subjected to online corona discharge using a roll-to-roll slit coating method. A wet film is formed on the flat surface of the processed PET gloss enhancement film substrate; The wet film is sequentially fed into the preceding oven temperature zone, the subsequent high-temperature oven temperature zone, and the UV curing substrate. The station was used for low-temperature positive pressure leveling, high-temperature negative pressure cationic curing, and free radical cross-linking curing, respectively, to obtain... To the final cured film; After the final cured film is stress-relieved by passing it through a cooling roller array, it is wound up under constant tension to form a film. The finished product is a high-efficiency brightness enhancement film.

6. The manufacturing method according to claim 5, characterized in that, The mixed solvent is composed of propylene glycol. The mixture consists of alcohol methyl ether acetate and butanone in a mass ratio of 60:40 to 80:

20.

7. The manufacturing method according to claim 5, characterized in that, The online corona treatment The processing intensity is 15–25 W·min / m², and the roll-to-roll slot coating operation speed is 15–30 m / min. The thickness of the dry film corresponding to the wet film is controlled to be 2.0 to 4.0 μm.

8. The manufacturing method according to claim 5, characterized in that, The temperature zone of the preceding oven The temperature gradient is set to 65–80°C, and the total residence time is 90–120 s; with the forced exhaust fan off, the internal temperature zone of the preceding oven is maintained at +30–+80 Pa. A positive pressure environment.

9. The manufacturing method according to claim 5, characterized in that, The subsequent high-temperature oven temperature The temperature in the zone is set at 105–115℃, and the dwell time is 40–60 seconds. With the exhaust fan on, maintain the internal temperature zone of the subsequent high-temperature oven at -150°C. A negative pressure environment of -300Pa is used to remove N,N-diisopropylethylamine.

10. The manufacturing method according to claim 5, characterized in that, The UV curing base station The internal environment is protected by nitrogen, with oxygen concentration controlled to less than 500 ppm, and the irradiation energy density of the ultraviolet light source is [not specified]. It ranges from 800 to 1200 mJ / cm². The temperature of the cooling roller array is 20-25℃, and the constant tension during winding is 50-80 N / m.